Zinc in Human Health - Rink, Lothar (IOS Press, 2014)
This comprehensive book provides a state of the art overview of the role of zinc as an essential trace element in human diet and its effect on human health. Since no storage system for zinc exists in the body, humans depend on daily intake and severe zinc deficiency is a problem in the developing world, whilst marginal zinc deficiency is a problem of developed countries. The first three chapters are an introduction to zinc research and its significance in human health. Six chapters follow on the role of zinc in cellular and molecular processes, their significance for an understanding of zinc biology and the measurement of zinc within these systems. The main section of the book, on zinc in health and disease, consists of 18 chapters on the specific role of zinc in different organ systems and connected diseases and the relevance of zinc in pregnancy, development and aging. The book ends with conclusions from transporter mutations for zinc physiology and a perspective on the future of zinc research. All of these contributions have been written by leaders in their respective fields. This is the first book to cover the subject comprehensively for 20 years